Multilingvismus v evropských zemích - Gajdíková, Kamila (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2025)
Multilingvismus je v evropských zemích běžným jevem, který má původ v historii a je umocněn existencí mezinárodních organizací, jako je Evropská unie. Mnoho zemí má více úředních jazyků, a ačkoliv jsou některé státy stále převážně jednojazyčné, situace se postupně mění se vzestupem angličtiny na pozici lingvy franky. Kromě výuky jazyků ve školách přispívá k vývoji a začlenění vícejazyčných mluvčích i imigrace. Cílem této práce je analyzovat vlivy používání více jazyků na jejich mluvčí a prozkoumat roli angličtiny jakožto lingvy franky i cizího jazyka. Pro účely této práce byl rozeslán dotazník, který se ptal občanů České a Slovenské republiky na jejich vzdělání a schopnosti v oblasti jazyků. Výsledky průzkumu prokázaly, že se z multilingvismu stává nový standard, a potvrdily status angličtiny jako lingvy franky a její vliv v dnešní době.

Multilingualism is a common phenomenon in European countries due to the continent’s history and existence of international organizations such as the European Union. Many countries have multiple official languages, and while some countries are still predominantly monolingual, the rise of English as lingua franca is changing the current situation. In addition to children being taught languages in schools, immigration also leads to development and further integration of multilingual speakers. The aim of this thesis is to analyse how the ability to use multiple languages affects the speakers, and further examine the role English plays both as a lingua franca and a foreign language. For the purpose of this thesis, a survey was conducted among Czech and Slovak citizens, asking them various questions about their language education and skills. The results prove that multilingualism is becoming the norm, and affirm the status of English as lingua franca and its influence in today’s world.
Multilingualism in European Countries
Keywords: Multilingvismus; Evropská unie; evropské jazyky; výuka jazyků; angličtina jako lingua franca; Multilingualism; European Union; European languages; language education; English as lingua franca